Producer Mobility Support Schemes for Named Data Networking: A Survey - Muktar Hussaini; Shahrudin Awang Nor; Amran Ahmad (Institute of Advanced Engineering and Science, 2018)
Mobile devices connectivity and data traffic growth requires scalable and efficient means of data distribution over the Internet. Thus, influenced the needs for upgrading or replacing the current Internet architecture to cater the situation as Named Data Networking (NDN) was proposed. NDN is clean-slate Internet architecture, proposed to replace IP with hierarchical named content that utilizes route aggregation to improve scalability and support mobility. Although, NDN provides supports for content consumer mobility with the help of catching capabilities, however, content producer faces many problems similar to mobility in IP architecture, such as, long handoff delay, unnecessary Interest packet losses and high bandwidth utilization. Hence, many concepts and schemes were proposed to address these problems. This paper reviewed and conceptually analyzed the schemes based on their fundamental design that broadly categorized into indirection-based approach, mapping-based approach, locator-based approach and control/data plane-based approach. In the review analysis, mapping-based approach schemes provide optimal path for packets delivery, high handoff delay Indirection-based and locator-based approach schemes provide normal handoff delay, but introduces tiangular routing path. The control/data plane-based approach schemes provide sub-optimal routing path and high handoff delay. The paper provided both strength and weakness of each scheme for further research.